2019
DOI: 10.1111/imj.14275
|View full text |Cite
|
Sign up to set email alerts
|

Opportunities to improve influenza vaccination rates in general medical inpatients

Abstract: Influenza vaccination is an important preventative health measure. A significant proportion of general medical inpatients meets indications for annual inactivated influenza vaccination (IIV), as recommended by the Australian National Immunisation Programme. This study explores opportunities to provide IIV to eligible general medical inpatients and associated barriers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Despite this, annual vaccine coverage rates in the community remain suboptimal, ranging from 44% to 82% 7 . A recent study at our institution during the 2017 influenza season found that amongst vaccine‐eligible patients admitted to the general medical unit, 33% were unvaccinated at admission and 28% were eligible for inpatient vaccination 8 . Opportunistic vaccination may serve as an important strategy to improve vaccine coverage.…”
Section: Overall Per Month Total Mean (Sd) Median (Iqr) Total Mean (Smentioning
confidence: 98%
See 3 more Smart Citations
“…Despite this, annual vaccine coverage rates in the community remain suboptimal, ranging from 44% to 82% 7 . A recent study at our institution during the 2017 influenza season found that amongst vaccine‐eligible patients admitted to the general medical unit, 33% were unvaccinated at admission and 28% were eligible for inpatient vaccination 8 . Opportunistic vaccination may serve as an important strategy to improve vaccine coverage.…”
Section: Overall Per Month Total Mean (Sd) Median (Iqr) Total Mean (Smentioning
confidence: 98%
“…This retrospective cohort study was approved by The Alfred Health Ethics Committee (Project No: 702/18) and by the Monash University Human Research Ethics Committee (Project No: 19162). The subjects included in the present study were derived from our previous cross‐sectional study, which comprised of a total of 200 patients admitted to the General Medical Unit at The Alfred Hospital, Melbourne, during the 2017 influenza season 8 . The methodology for recruitment and data‐analysis was previously described by Zaman et al 8 .…”
Section: Overall Per Month Total Mean (Sd) Median (Iqr) Total Mean (Smentioning
confidence: 99%
See 2 more Smart Citations